Ralstonia solanacearum – a New Threat to Potato Production in Serbia - Milijašević-Marčić, Svetlana; Todorović, Biljana; Potočnik, Ivana; Rekanović, Emil; Stepanović, Miloš; Mitrović, Jelena; Duduk, Bojan (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2013)
A survey of ware potatoes (a total of 1127 samples) from localities in Serbia during two consecutive years resulted in detection and identification of R. solanacearum in 17 tuber samples. The monitoring detected the causal agent of bacterial wilt and brown rot of potato in three districts of Vojvodina province. In 2011, the infection by R. solanacearum was confirmed in 7 samples of ware potato tubers (varieties – Saturna, Pirol, Hermes, Panda) in West Bačka and South Bačka Districts. In 2012, the infection by R. solanacearum was confirmed in 10 potato tuber samples (Lady Claire, Desiree, Panda, Red Fantasy and Vineta varieties) from two districts: South Bačka and Central Banat. Bacterial strains obtained from positive samples were identified as R. solanacearum biovar 2 using PCR/RFLP analysis, pathogenicity test on tomato transplants, and nutritional, enzymatic and biovar determination tests. To our best knowledge, these are the only findings of R. solanacearum infection in ware potatoes in Serbia. R. solanacearum was not detected in tomato or any other host plant tested in this study. Furthermore, the bacterium was not found in any of the water samples tested, including those originating from areas in which the bacterium was found in ware potato samples.